A Rare Presentation of a Rare Disease: Pulmonary Lymphomatoid Granulomatosis - Ghulam Rehman Mohyuddin; Fatima Sultan; Ghulam Khaleeq (Case Reports in Pulmonology)
A 70-year-old female presented with a 4-week history of dry cough and wheezing. Chest radiograph showed a 10.5 cm mass-like density in the anterior mediastinum which had not been previously visualized. Computed tomography scan (CT) of the chest showed a right hilar mass encasing and narrowing right upper lobe bronchus and right mainstem bronchus and secondary atelectatic changes. Biopsy was consistent with a diagnosis of lymphomatoid granulomatosis Grade 3. She responded well clinically and radiologically to therapy. Lymphomatoid granulomatosis is a rare EBV-associated disorder which is considered a lymphoproliferative disease. The most common radiographic feature is multiple lung nodules. An isolated hilar mass is an exceptionally rare presentation of this rare disease.